Effectiveness of Waste Management in the United States of America - Yuestika Kerenhapukh; Ananda Fadhila; Henna Notrian Puteri; Putri Fadilah; Abdul Halim (Andalas Institute of International Studies, 2021)
Waste is a significant concern at this time. No matter what country, waste will always exist in people's daily lives, including the United States. To deal with all types of waste, the United States has implemented policies and regulations called the Environmental Protection Agency (EPA) and 3R.This study aims to see how the policies launched by the United States, namely the Environmental Protection Agency and 3R, in dealing with environmental problems, where one of the causes is that it comes from various types of waste, both from the household sector and large companies. In writing this journal, the author uses a descriptive-qualitative research method based on green theory. The environmental crisis has penetrated almost all parts of the world since the 60s, starting from an individual protest until finally, this environmental problem has become an international concern; green theory is present as a form of concern for the environment because the environment is the world's primary asset, so by saving the environment indirectly also save the inhabitants of the earth. Each country is competing in finding ways to overcome these problems. One of which is the United States. The environmental protection agency and 3R are some of the steps taken by the United States in dealing with environmental problems in the hope that the policies taken can save them from environmental problems not only in the present but also in the future, where several factors cause these problems. In this program, the United States implements several activities. The most important is providing education about the dangers of waste and recycling waste in the environment. This is done in response to the environmental crisis, which is the leading cause of damage and life crises, including disease. In this paper, the authors also see how effective Environmental Protection Agency policies are and describe several types of waste that damage the environment.